Root Canal Treatment of Severely Calcified Teeth with Use of Cone-Beam Computed Tomography as an Intraoperative Resource: New strategies for root canal treatment of severely calcified teeth with use of intraoperative CBCT - Quaresma, Sérgio André; Costa, Rui Pereira da; Petean, Igor Bassi Ferreira; Silva-Sousa, Alice Corrêa; Mazzi-Chaves , Jardel Francisco; Ginjeira, Antonio; Sousa-Neto, Manoel Damião (Iranian Endodontic Journal, 2022)
The aim of this study was to describe a new strategy, consisting of the use of cone-beam computed tomography (CBCT) in the planning and intraoperative stages of root canal treatment (RCT), associated with the use of radiopaque gutta-percha markers, as an auxiliary tool in the location of severely calcified root canals. Three cases involving anterior and posterior teeth with severe calcification of the root canal were submitted to initial periapical radiographic and CBCT evaluations for diagnosis and planning of the operative steps. In a first intervention, when the location of the canal orifice was not successful, radiopaque markers were inserted in the suggested position of canal orifice with the aid of magnification and the use of ultrasonic devices, in order to perform an intraoperative CBCT analysis that allowed dynamic navigation through the static position of markers. The association of intraoperative CBCT with radiopaque markers allowed the location of the canal orifice and the following RCT execution. The use of CBCT in two different moments of RCT allowed the diagnosis of three-dimensional anatomical variations of root canal. Add, when associated with the use of radiopaque gutta-percha markers, acted as an auxiliary tool in the location of the canal orifice of calcified canals. Therefore, the presented strategy provides the clinician the precision that cases with calcification require and give an important contribution to treatment predictability.